Peranan Audit Operasional dalam Pemeriksaan Sumber dan Penggunaan Dana pada PT. BPR Eka Prasetya Medan - Liskauli Sinaga; Zainal Abidin; Rosmaini Rosmaini (Mahesa Research Center, 2023)
xThe purpose of this study was to determine the role of operational audit in examining sources and uses of funds at BPR Eka Prasetya Medan. The formulation of the problem in this study is